Assessing Drug Interaction and Pharmacokinetics of Loxoprofen in Mice Treated with CYP3A Modulators - Sanjita Paudel; Aarajana Shrestha; Piljoung Cho; Riya Shrestha; Younah Kim; Taeho Lee; Ju-Hyun Kim; Tae Cheon Jeong; Eung-Seok Lee; Sangkyu Lee (Pharmaceutics, 2019)
Loxoprofen (LOX) is a non-selective cyclooxygenase inhibitor that is widely used for the treatment of pain and inflammation caused by chronic and transitory conditions. Its alcoholic metabolites are formed by carbonyl reductase (CR) and they consist of trans-LOX, which is active, and cis-LOX, which is inactive. In addition, LOX can also be converted into an inactive hydroxylated metabolite (OH-LOXs) by cytochrome P450 (CYP). In a previous study, we reported that CYP3A4 is primarily responsible for the formation of OH-LOX in human liver microsomes. Although metabolism by CYP3A4 does not produce active metabolites, it can affect the conversion of LOX into trans-/cis-LOX, since CYP3A4 activity modulates the substrate LOX concentration. Although the pharmacokinetics (PK) and metabolism of LOX have been well defined, its CYP-related interactions have not been fully characterized. Therefore, we investigated the metabolism of LOX after pretreatment with dexamethasone (DEX) and ketoconazole (KTC), which induce and inhibit the activities of CYP3A, respectively. We monitored their effects on the PK parameters of LOX, cis-LOX, and trans-LOX in mice, and demonstrated that their PK parameters significantly changed in the presence of DEX or KTC pretreatment. Specifically, DEX significantly decreased the concentration of the LOX active metabolite formed by CR, which corresponded to an increased concentration of OH-LOX formed by CYP3A4. The opposite result occurred with KTC (a CYP3A inhibitor) pretreatment. Thus, we conclude that concomitant use of LOX with CYP3A modulators may lead to drug−drug interactions and result in minor to severe toxicity even though there is no direct change in the metabolic pathway that forms the LOX active metabolite.